Quasi-static indentation analysis on three-dimensional printed continuous-fiber sandwich composites. (February 2021) - Dikshit, Vishwesh; Nagalingam, Arun Prasanth; Goh, Guo Dong; Agarwala, Shweta; Yeong, Wai Yee; Wei, Jun
Fiber reinforced sandwich structures are widely used as structural elements due to their lightweight and high load-bearing capacity. In this paper, effort is taken to fabricate fiber facesheet (0°/90° orientation) and corrugated cores (trapezoidal vertical pillared, core-1 and sinusoidal vertical pillared, core-2) of the sandwich structure using fused filament fabrication and Inkjet printing techniques, respectively. Firstly, the quasi-static indentation properties of the additively manufactured facesheet, cores, and sandwich structures were investigated. In addition, acoustic emission signals were monitored during quasi-static indentation testing and the resulting hits data were correlated with quasi-static indentation test results. The quasi-static indentation test results showed that sinusoidal sandwich structures have the highest load-bearing capacity of 1.79 kN until crack initiation and a total energy-absorption capacity of 20.05 J. Acoustic emission hits recorded in the range of 1–30, 30–100, and above 100 represented crack initiation, crack propagation, and specimen failure, respectively. Lastly, micro-computed tomography analysis was performed on the sandwich structures at intermediate indentation displacements, thus leading to the identification of hard to detect failure points and damage propagation. Fracture surface morphology of the sandwich structures showed that fiber pullout and core shear were the dominant damage mechanisms.